International donor agencies and humanitarian aid in Adamawa, Borno and Yobe States of Northeastern Nigeria / Usman Sambo and Babayo Sule - Sule, Babayo; Sambo, Usman (Universiti Teknologi MARA, 2020)
International donors are non-profit and mostly non-governmental organisations that are dedicated to developmental and humanitarian services to mankind across the globe particularly in the developing countries where the needs are more urgent and the condition is becoming unbearable due to armed conflicts and other social disasters. The Northeastern Nigeria is one of the most affected areas in the world currently on humanitarian situation which is making life difficult for the inhabitants. The international donor agencies are operating in Northeastern Nigeria to provide humanitarian aids to more than 3 million affected victims of the Boko Haram insurgency and violence specifically against women and children. The study examined the role of international humanitarian aid in alleviating the human suffering in Northeastern Nigeria and the level of successes and challenges encountered in the process. The study used both the primary and secondary sources of data for the research. The primary data was the use of an in-depth interview where selected informants from the stakeholders in the area of study were identified and consulted for the interview. The secondary sources consist of books, journal articles, newspapers and internet sources. The data obtained were discussed, analysed and interpreted using content analysis in which themes were identified and discussed. The research discovered that humanitarian aid from international donors succeeded in averting many disasters in Northeastern states of Adamawa, Borno and Yobe despite the fact that there is still a large number that is in critical need of assistance but not accessible due to the security situation. The research recommends among others that all stakeholders must cooperate in harmonising the common cause for effective delivery of aid services to the affected victims.